SPIRITUALITAS DALAM SINKRETISME ISLAM DAN SAPTA DARMA - Wiwik Setiyani Khasbullah; Khoirun Nisa’ (UIN Antasari Banjarmasin, 2021)
Every adherent of a religion or belief has a certain way to get closer to God. A strong desire to be close to God the creator of nature is a spirituality that can change human behavior for the better. The meeting between Islam and Sapta Darma is a way to find inner calm which has the concept of physical and spiritual awareness. Hence this article wants to explain the form of syncretism between Islam and Sapta Darma in Surabaya in the form of prostration or ening. The prostration performed by Sapta Darma is not a prayer, but a special ritual of seeking tranquility in the experience of life as a cultural interpretation. Prostration in Islam is the implementation of prayer to get closer to Allah with the provisions taught in Islam. This study uses in-depth interview as methodology to find the stage of religious maturity from the aspect of Shari'a and the implementation of religious teachings. This Research finds that, even though the syncretism between Islam and Sapta Darma is so pronounced but, this condition encourages its followers to maintain the two because they find what they want to achieve namely, balance and spiritual well-being. It shows that Islam and Sapta Darma are not as an escape but, as a way of life. This study also aims to provide a new perspective or paradigm in understanding religious concepts and spiritual values through syncretism between Islam and Sapta Darma. Syncretic diversity has been attached to society and has become the cultural identity of its locality.Setiap penganut agama atau kepercayaan memiliki cara tertentu untuk mendekatkan diri dengan Tuhannya. Keinginan yang kuat untuk dekat dengan Tuhan pencipta alam merupakan spiritualitas yang mampu mengubah perilaku manusia menjadi lebih baik. Pertemuan antara Islam dan Sapta Darma menjadi jalan untuk menemukan ketenangan batin yang memiliki konsep kesadaran jasmani dan rohani. Artikel ini menjelaskan bentuk sinkretisme antara Islam dan Sapta Darma di Surabaya, dalam bentuk sujud atau ening. Sujud yang dilakukan Sapta Darma bukanlah pelaksanaan sholat tetapi, ritual khusus mencari ketenangan dalam pengalaman hidup sebagai interpretasi budaya. Sujud dalam Islam adalah pelaksanaan sholat untuk mendekatkan diri kepada Allah dengan ketentuan yang diajarkan dalam Islam. Studi ini menggunakan metode in-depth interview guna, menemukan tingkat kematangan dalam beragama dari aspek syariat dan implementasi ajaran agama. Temuan penelitian menunjukan, kendati sinkretisme antara Islam dan Sapta Darma begitu terasa namun, kondisi ini mendorong mereka tetap mempertahankan keduanya karena, menemukan apa yang ingin dicapai yaitu, keseimbangan dan kesejahteraan spiritualitas. Agama Islam dan Sapta Darma bukan sebagai pelarian hidup semata tetapi, paradigma baru untuk memahami konsep keberagamaan dan nilai-nilai spiritualitas umat beragama melalui sinkretisme Islam dan Sapta Darma. Keberagamaan sinkretis telah melekat pada masyarakat dan menjadi identitas budaya lokalitasnya.